Fast and sensitive fluorescent detection of inorganic mercury species and methylmercury using a fluorescent probe based on the displacement reaction of arylboronic acid with the mercury species. Issue 19 (10th February 2020) - Neupane, Lok Nath; Park, Joohee; Mehta, Pramod Kumar; Oh, Eun-Taex; Park, Heon Joo; Lee, Keun-Hyeung
Abstract : We present a reaction-based fluorescent probe for Hg 2+ and methylmercury based on the displacement reaction of arylboronic acid with mercury species. Abstract : We present a reaction-based fluorescent probe (1 ) for Hg 2+ and CH3 Hg +, based on the displacement reaction of the arylboronic acid with the mercury species. 1 showed promising sensing properties for Hg 2+ and CH3 Hg +, such as high selectivity and sensitivity, turn-on response, fast response to Hg 2+ (<2 min) and CH3 Hg + (<5 min), low detection limits and operation in purely aqueous solutions.